POST-TRAUMATIC STRESS DISORDER: UNDERSTANDING, IMPACTS, AND COPING STRATEGIES FROM ACADEMIC AND COMMUNITY PERSPECTIVES - Barbosa, Felipe Vieira; Leal, Marina Sias; Feijó, Rosane Pinheiro Krüger (Seven Editora, 2026)
Post-Traumatic Stress Disorder (PTSD) is a psychological condition resulting from exposure to traumatic events that leads to persistent cognitive, emotional, and behavioral changes, compromising the individual’s quality of life. Although trauma has been studied since Ancient Greece, the current understanding, focused on emotional and memory aspects, was consolidated in the 20th century, culminating in its current classification in the DSM-5-TR within trauma- and stressor-related disorders. The disorder shows a high prevalence among women, survivors of sexual violence, and rescue professionals, presenting neurobiological alterations that impair memory consolidation and functions such as attention. This study, linked to the Academic League of Psychology and Health (LAPS) at the Catholic University of Pelotas, aimed to analyze PTSD through a bibliographic and cultural review, combining theoretical foundations with extension practices. The methodology included the study of theoretical and audiovisual references, as well as a community action in the Laranjal neighborhood, in Pelotas, consisting of mapping service areas and distributing informational materials. The results indicate that the activity allowed for a deeper understanding of diagnostic criteria and promoted community support, bringing academic knowledge closer to society. It is concluded that the increase in global tragedies raises the risk of developing the disorder, making interdisciplinary initiatives essential for disseminating qualified information and strengthening coping strategies.